1999
DOI: 10.1093/nar/27.21.4251
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive mining of EST libraries for genes differentially expressed in normal and tumour tissues

Abstract: A four-step procedure for the efficient and systematic mining of whole EST libraries for differentially expressed genes is presented. After eliminating redundant entries from the EST library under investigation (step 1), contigs of maximal length are built upon each remaining EST using about 4 000 000 public and proprietary ESTs (step 2). These putative genes are compared against a database comprising ESTs from 16 different tissues (both normal and tumour affected) to determine whether or not they are differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
80
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 32 publications
0
80
0
2
Order By: Relevance
“…By statistical evaluation of the frequency of the sequences for specific genes it is possible to develop an expression profile at different environmental conditions for genes of different cDNA libraries. Thereby it is possible to investigate the up-and down regulation of genes (Schmitt et al, 1999) or to compare the gene expression under different conditions (Rafalski et al, 1998). The establishment of ESTs from E. huxleyi at different stages of viral infection could thus be an effective means for expression analysis of virus infected cultures for which the viral genome is known.…”
Section: Introductionmentioning
confidence: 99%
“…By statistical evaluation of the frequency of the sequences for specific genes it is possible to develop an expression profile at different environmental conditions for genes of different cDNA libraries. Thereby it is possible to investigate the up-and down regulation of genes (Schmitt et al, 1999) or to compare the gene expression under different conditions (Rafalski et al, 1998). The establishment of ESTs from E. huxleyi at different stages of viral infection could thus be an effective means for expression analysis of virus infected cultures for which the viral genome is known.…”
Section: Introductionmentioning
confidence: 99%
“…In all, 40% of primary breast tumors exhibited aberrant methylation of TMS1 (Conway et al, 2000). TMS1 was also identified in an 'in silico' screen for mRNAs that were under-represented in breast cancer cDNA libraries (Schmitt et al, 1999). In a recent large-scale gene expression profiling study, TMS1 was found to be downregulated by at least twofold in 27 of 117 primary breast tumors (van 't Veer et al, 2002).…”
mentioning
confidence: 99%
“…With respect to the identification of cancer-associated gene products with potential relevance to cancer vaccine targets, EST database mining has resulted in the discovery of a prostate cancer-related gene, PAGE-1/GAGE-B, 16 a Ewing's sarcoma-associated gene, XAGE-1, 17 and a number of differentially expressed transcripts in breast cancer 18 and glioblastoma multiforme. 19 In order to identify new CT gene products, the current study mined the Unignene database, a compilation of both EST and Genbank databases, for transcripts expressed exclusively in cancer and normal testis.…”
mentioning
confidence: 99%